Spirituality and Religiousness of Secondary School Students in a Public and Catholic School - Marzena Chrost; Sławomir Chrost (Ignatianum University Press, 2024)
Research objectives: The aim of this article is to investigate and analyse spirituality and religiousness in secondary school students of a public and a Catholic school. Research methods: The diagnostic survey method with a questionnaire was applied in the empirical research. The empirical data was collected with the authors' original questionnaire on spirituality and religiousness of youth, based on publications by Janusz Mariański and Halina Mielicka. The following statistical methods were used to analyse the research material: Student's t-test, chi2 correlation test, Fisher's exact test, one-way analysis of variance (ANOVA), Tukey's post hoc test and Fisher's linear trend test. A p-level of <0.05 was considered statistically significant and a p-level of <0.01 was considered highly significant. Structure of the article: The spirituality and religiousness of young people is an important issue in school education. Therefore, the article discusses, with reference to the literature on the subject, the basic concepts of spirituality and religiousness. The status of the existing research is shown. The methodological assumptions of our own research are discussed, as well as the characteristics of the study group with respect to the division into a public and a Catholic school. The results and statistical analysis, as well as the limitations of the research, are presented. Finally, general conclusions from the research are presented. Research results: The research was conducted in 2023. A total of 555 secondary school students participated in the study, including 341 (61.44%) from a Catholic school and 214 (38.56%) from a public school in Krakow. There were more females (58.74%) than males (41.26%) in the study group. Most of the young people (54.95%) declared that they are believers, and most of the believers (85.41%) declared that they are Catholic. The results on the spirituality scale differed significantly (p<0.05) between the groups; they were higher among the Catholic school students. Similarly, scores on the religiousness scale were highly significantly different (p<0.01) between the groups and higher in the Catholic school. Conclusions and recommendations: Based on the study significant relationships were observed between the type of school and the level of spirituality and religiousness, as well as between the declaration of faith and the level of spirituality and religiousness. The results of the research indicate that spirituality and religiousness are related to each other. Undoubtedly, attending a religious school can be a valuable contribution to developing the religious/spiritual sphere in a young person. It would be worthwhile to conduct further, detailed research on adolescents' religiousness and spirituality in future in order to better understand and describe this issue.